Sexuality of elders with dementia: social representation of nursing students - Wanderson Carneiro Moreira; Vanessa Carvalho Fontinele; Fernanda Cláudia Miranda Amorim; Maria do Perpétuo Socorro de Sousa Nóbrega; Cláudia Maria Sousa de Carvalho; Camila Aparecida Pinheiro Landim Almeida (Universidade Federal do Ceará, 2020)
Objective: to learn about the social representation of nursing students about the sexuality of elders with dementia. Methods: qualitative study, based on the Theory of Social Representations, developed with 20 Nursing Graduation students from a Brazilian higher education institution. Data was collected through a focal group, processed in the software IRAMUTEQ and analyzed using a Descending Hierarchical Classification. Results: four semantic classes emerged: Sexuality as a right, The theme was insufficient in graduation, Meanings attributed to sexuality, and Care from the perspective of students. Conclusion: the study showed that the nursing students investigated had polysemic representations about the sexuality of elders with dementia, among which discriminatory and stigmatizing conceptions stood out, socially constructed and anchored in common sense.